Online interaction dynamic in validating the identity of being a K-Pop fan through merchandise / Nur Maizatul Balqis Mohamad Mustaza - Mohamad Mustaza, Nur Maizatul Balqis (2023)
This study attempted to identify the value, meaning and symbols of the official K-Pop products and merchandise towards the fans in terms of sense of identity and belonging. Merchandise is widely used in the world of K-Pop among K-Pop fans particularly. However, very few people have discussed how merchandise might serve as items that reveal the identities of K-Pop fans and how it might inspire a sense of devotion from K-Pop fans to their favorite idols. For this reason, the author used the dynamics of online fans interaction on Twitter, which most K-Pop fans use frequently to engage with one another and stay up to date on the activities of their idols, to find evidence of how the merchandise affects K-Pop fans' identities. This thesis first verified each participant's identity on Twitter to ensure that they are authentic K-Pop fans. Subsequently, data on conversations and discussions among K-Pop fans regarding merchandise are gathered based on specific keywords related to the study and presented. The analysis of every K-Pop fan's Twitter conversation ultimately result in the discovery of data that supported all previous studies and provided answers to the research's open-ended questions. The experiment's findings demonstrated that K-Pop fans have certain characteristics that influence how they use merchandise to affirm their identity and justify their collecting of K-Pop merchandise. The thesis asserted that those characteristics reinforced a sense of identity and belonging, which would increase K-Pop fans' devotion to their idols through merchandise.